Peningkatan kinerja tenaga administrasi: Sebuah studi tentang faktor pelatihan dan pengembangan - Sirait, Marisca Yessica; Anatan, Lina (Universitas Kristen Maranatha, 2023)
This article aims to examine the effect of training and development on the performance of administrative staff at Universitas Kristen Maranatha. This study involved 70 administrative staff as samples. A quantitative approach is used with data collection using a questionnaire and data analysis using SPSS software version 26. To test the hypothesis, this study used multiple linear analysis. The study found that training affects the performance of administrative staff at Universitas Kristen Maranatha positively and significantly, and development also affects the performance of administrative staff at Universitas Kristen Maranatha positively and significantly. Training and development have a positive impact on the performance of administrative staff at Universitas Kristen Maranatha. The more planned the training and development program, the more it will affect the performance of administrative staff.